EMPLOYMENT OF THE DISABLED - Kuleshov, Georgyi; Zhesterov, Pavel; Volkova, Maria; Neznamova, Alla; Lenkovskaya, Renata (Revista Inclusiones, 2020)
The article deals with legal aspects and explores the problems of employment of the disabled on the basis of law enforcement practice. It also provides a detailed overview of current Russian legislation and analyzes the key international legal acts that establish the basic principles of legal regulation of employment of the disabled, as well as corresponding national regulatory legal acts. Based on the analysis, the probabilistic forms of discrimination manifestation in the process of work and the implementation of employment of the disabled, differentiated by individual areas of activity, have been determined